Long and short-run impacts of CEO narcissism on the nexus between financial performance and environmental and social governance: Evidence from new quantile-based panel cointegration and causality techniques - Bildirici, Melike E.; Ersin, Ozgueromer Omer; Fidan, Selahaddin Samil (ELSEVIER SCI LTD, 2024)
This study investigates the crucial but understudied relationship between chief executive officer (CEO) narcissism, and environmental, social, and governance (ESG) performance in addition to the effects of financial performance. The study examines the nexus for their long-run and short-run associations and for quantile-specific effects including causality linkages that were governed by different levels of CEO narcissism for a sample of 55 energy companies from the United States for the 2003-2022 period. Novel Panel Autoregressive Distributed Lag and Panel Quantile Granger Causality methods are employed to encounter two modeling strategies. The model utilizes two newly proposed proxy variables for measuring CEO narcissism, namely, Policy Bribery and Corruption Scores (BC), and, Audit Fees (AF). Empirical findings with all CEO narcissism measures under different modeling strategies indicated positive and significant effects of CEO narcissism on ESG for all quantiles in the long run asymmetrically from the lowest levels towards higher levels of CEO narcissism with varying but positive magnitudes with an exception: at the highest quantile, the effect on ESG performances becomes reversed, indicating very high levels of CEO narcissism harming ESG performances. The short-run results also confirm these relations, confirming the effects of CEO narcissism at different levels with varying magnitudes. Quantilespecific causality tests determined causality from CEO narcissism to ESG performance in all quantiles without exception across different scenarios. Between financial performance and ESG there is a unidirectional causality from financial to ESG variables in 2nd, 4th and 5th, and, bidirectional causality at the 1st quantile. Further, CEO narcissism is the Granger-cause of financial performance in all quantiles. The new CEO narcissism variables are compared and tested statistically for robustness with traditional CEO narcissism measures of Chatterjee and Hambrick (2007, 2011). The findings of the proposed model and new CEO narcissism variables capture the dynamic changes in CEO narcissism in time and at different levels more effectively than the traditional CEO narcissism measure. The fresh finding led to a set of policy recommendations.
Keywords: CEO narcissism; ESG; CSR; Panel quantile regression; ARDL; Financial performance; Causality; Panel quantile ARDL; LAGRANGE MULTIPLIER TEST; GRANDIOSE NARCISSISM; FIRM PERFORMANCE; RENEWABLE ENERGY; CFO NARCISSISM; UPPER ECHELONS; RISK-TAKING; PERSONALITY; RESPONSIBILITY; BRIGHT; Science & Technology - Other Topics; Engineering; Environmental Sciences & Ecology